2014
DOI: 10.5897/ajb11.2298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen on rice yield, yield components and quality parameters

Abstract: 99 g). Among the different N application levels, significant difference was observed in all quality parameters except gelatinization temperature (GT); the highest amylose content (AC) was obtained from treatment N1 and significantly highest gel consistency (GC) was obtained from treatment N3. In general, GC was increased with N-fertilizer application and only result was changed from N3 to N4 and was reduced. Whereas AC was reduced from N1 to N3, and the result was reversed from N3 to N4. Meanwhile, the interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…Previous studies have reached different conclusions on yield-related parameters (number of spikelets per panicle, grain filling percentage, and grain weight), which either increased ( Jian et al 2014 ), were not affected ( Mandana et al 2014 ), or even decreased ( Li et al 2014 ), following the application of N fertilizer. These phenomena might be explained by our experimental results.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have reached different conclusions on yield-related parameters (number of spikelets per panicle, grain filling percentage, and grain weight), which either increased ( Jian et al 2014 ), were not affected ( Mandana et al 2014 ), or even decreased ( Li et al 2014 ), following the application of N fertilizer. These phenomena might be explained by our experimental results.…”
Section: Discussionmentioning
confidence: 93%
“…YosefTabar (2013) reported that the application of N and P fertilizer increased the number of grain, weight of 1000 grain and yield of rice. Another studies noted that application N fertilizer increased panicle per hill, total grains per panicle (Haque & Haque, 2016), weight of 1000 grains and yield of the grain (Haque & Haque, 2016;Mandana, Akif, Ebrahim, & Azin, 2014;YosefTabar, 2013). Arivazhagan et al (2011) reported that the application of fly ash at 50 tha-1 increased the yield of cereal crops from 5-20%, vegetable crop from 5-20%, plantation crops from 20-30%, rice crop 13-17%, sugarcane crop from 15-30%, maize crop from 36-40% and potato crop from 25-37% over control.…”
Section: Copyright © 2018 Universitas Brawijayamentioning
confidence: 97%
“…The crop occupies onethird of the world's total area planted to cereals and provides 35 to 60% of the calories consumed by 2.7 billion people. (Mandana et al, 2014). The production of an economic crop of rice without high rates of mineral fertilizers suitable for new varieties of rice distinguished in the high yield in the soil is poor content of organic matter is one of the most important challenges faced by researchers, especially in Egypt.…”
Section: Introductionmentioning
confidence: 99%